ANALISIS PEMBERDAYAAN EKONOMI KOPERASI DAN USAHA KECIL MENENGAH (UKM) MASYARAKAT DI KECAMATAN TANJUNGSARI KABUPATEN SUMEDANG - Dindin Awaludin (Journal Of Regional Public Administration (JRPA), 2018)
This study aims to find out, get objective data and information about the economic empowerment of cooperatives and small and medium businesses (UKM) in the District of Tanjungsari Sumedang Regency. In this case the researcher traced through the Economic Empowerment Model. The method used in the preparation of this report is a qualitative method (naturalistic setting) with descriptive type. Determination of targets is taken by using purposive sampling technique where the object is implementing the policy with certain considerations. Samples used in this study were 5 people, namely the Sub-District Chief, Head of Program and Finance, Head of Governance Section, Head of Community and Village Empowerment Section, Head of Development Section, and the community. Data collection techniques through primary data collection techniques such as observation and interviews, secondary data collection techniques such as literature studies and documentation. The data processing procedures used are the Miles and Huberman model with steps: data reduction, data presentation, concentration drawing / verification and triangulation. Based on the results of the study it was concluded that the economic empowerment of cooperatives and community SMEs in Tanjungsari Subdistrict, Sumedang Regency is said to be quite optimal, this can be seen from several obstacles, namely the community's understanding that is still lacking in understanding about the cooperatives and SMEs and the lack of employee socialization to the community. Efforts to overcome obstacles, namely employees can provide understanding to the community about the use of cooperatives and SMEs, and employees must further increase their socialization activities well, the objectives of the cooperative program and community SMEs must be realized properly, namely by improving the performance and quality of products to be marketed and the government in providing motivation to the community regarding cooperatives and community SMEs conducting counseling, meetings, deliberation and sharing / sharing with the community.